NILAI-NILAI GOTONG-ROYONG DALAM MASYARAKAT PETANI PADI SAWAH DI DESA SUNGAI SIPUT KECAMATAN SIAK KECIL KABUPATEN BENGKALIS - Siti Julaikha; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This study titled Values In Mutual-Aid Society of Rice Farmers in the village of River Snail Bengkalis District of Siak Kecil. This study aims to describe whether the values of mutual assistance is still done in a rice paddy farming communities and whether these values reliable in the face of risk and uncertainty in the lives of lowland rice farmers in the village of River Snail Bengkalis District of Siak Kecil.The method used to analyze these data quantitatively performed, then the data collected is presented descriptively tells the results of research by using logical sentences to be understood. The sampling technique used in this research is to use Probability Sampling Technique and using simple random sampling (simple random sample) that each individual household in the population is given an equal opportunity to be selected as a member of the sample so that eventually acquired as many as 45 samples of rice paddy farmers.This research was conducted in the village of River Snail Bengkalis District of Siak Kecil. The results of the study showed that the values of mutual assistance was conducted in lowland rice farming community life. Where mutual assistance activities consist of voluntary mutual aid as mourn the dead and cooperation for mutual help and reciprocity as Rewang activities, social gathering activities and activities working the fields. The existence of mutual assistance is a strategy in the face of risk and uncertainty in the lives of lowland rice farmers as income levels fluctuating, uncertain climate, the threat of pests of rice, the price of which is not certain marketing and capital resources are not there.Keywords: Mutual-Aid, Values and Rice Farmers.